Resveratrol and inflammatory bowel disease: the evidence so far - Nunes, Sandra; Danesi, Francesca; Del Rio, Daniele; Silva, Paula (Nutrition research reviews, 2018)
Despite the fact that inflammatory bowel disease (IBD) has still no recognised therapy, treatments which have proven at least mildly successful in improving IBD symptoms include anti-inflammatory drugs and monoclonal antibodies targeting pro-inflammatory cytokines. Resveratrol, a natural (poly)phenol found in grapes, red wine, grape juice and several species of berries, has been shown to prevent and ameliorate intestinal inflammation. Here, we discuss the role of resveratrol in the improvement of inflammatory disorders involving the intestinal mucosa. The present review covers three specific aspects of resveratrol in the framework of inflammation: (i) its content in food; (ii) its intestinal absorption and metabolism; and (iii) its anti-inflammatory effects in the intestinal mucosa in vitro and in the very few in vivo studies present to date. Actually, if several studies have shown that resveratrol may down-regulate mediators of intestinal immunity in rodent models, only two groups have performed intervention studies in human subjects using resveratrol as an agent to improve IBD conditions. The effects of resveratrol should be further investigated by conducting well-designed clinical trials, also taking into account different formulations for the delivery of the bioactive compound.